A THE ROLE OF SOCIO PSYCHOLOGICAL APPROACH TO CONFLICT RESOLUTION IN MAINTAINING (INTER) NATIONAL PEACE AND STABILITY - Fritzhand, Ana; Tashkovski, Igor (International Scientific Journal Vision, 2018)
Confl icts, as it is already well documented, are inevitable part of people’s existence. They are neutral in their nature. Whether their outcome is positive or negative, depends on the approaches applied for their resolution. International confl icts, which are processes that aff ect international relations, also pervade the whole society. Therefore, when analyzing confl icts various dimensions should be accounted for. They include, but are not limited to, strategic, military and diplomatic, as well as the economic, psychological and cultural dimensions. All of these aspects interact with each other and defi ne both intrasocietal and intersocietal processes that drive the confl ict. This paper addresses several propositions about the nature of international confl icts which, according to Kelman (2007), are coming from the social-psychological perspective. One proposition is that international confl icts are processes driven from collective needs and fears. The other propositions claim that these confl icts are intersocietal, multifaceted processes of mutual infl uence, while in the same time they are interactive processes with an escalatory, self-perpetuating dynamics. As the same author points out, a new form of practice of international confl ict resolution, called interactive problem solving, is based on social-psychological principles. We further analyze the potential of socio-psychological approach in resolving confl icts non-violently, by providing better understanding of the nature of confl ict and highlighting the eff ective ways for building a culture of peace and thus maintaining peace and stability nationally and internationally.